Principal Leadership in Fostering Positive Discipline through the Restitution Triangle in Elementary Schools - Julita Julita; Marwan Marwan; Aminah Aminah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study examines the methods employed by school principals to promote constructive discipline via the restitution triangle in public elementary schools within the Tangse District of Pidie Regency. Data were acquired through observations, semi-structured interviews, and document analysis involving principals, teachers, students, and parents, utilizing a qualitative field study approach. The results demonstrate that the execution of the restitution triangle is still in a nascent and disjointed phase. Principals have commenced restorative procedures via reflective discussion and coaching; however, these initiatives lack consistency and have not yet been properly assimilated by teachers. Conventional punitive disciplinary methods prevail, indicating a restricted comprehension of restorative ideas. Notwithstanding these limitations, initial beneficial outcomes were observed, such as increased timeliness, heightened professional accountability, and improved communication among educators. Significant obstacles are inadequate professional development, ineffective supervisory systems, and a school culture that lacks comprehensive alignment with restorative principles. The study illustrates that the restitution triangle serves as an effective and humane framework for enhancing positive discipline in elementary schools, contingent upon ongoing leadership commitment, systematic capacity development, and a collaborative school culture